Cerebral developmental venous anomalies in children with mismatch repair deficiency - Kara, Buket; Paksoy, Yahya; Çağlayan, Ahmet Okay; Seher, Nusret; Akbaş, Hilal; Köksal, Yavuz (The Turkish Journal of Pediatrics, 2022)
Background. Constitutional mismatch repair deficiency (CMMRD) is one of the rare cancer predisposition syndromes. The aim of this study was to evaluate the cerebral developmental venous anomalies in children with central nervous system tumors associated with CMMRD, an area in which there is extremely little experience. Methods. Data from children diagnosed with medulloblastoma and high grade central nervous sytem tumor were retrospectively collected. According to the European CMMRD criteria, nine patients were diagnosed as CMMRD syndrome and the others consisted of the group without CMMRD. All radiological examinations of these children were retrospectively reviewed. Whole exome sequencing was performed to index cases` germline DNA. Results. Nine children from four families, six females and three males, were studied. The median age at the first tumor diagnosis was 4.5 years (range, 9 months to 14 years). All CMMRD patients had café au lait spots, but none fulfilled the diagnostic criteria for neurofibromatosis. The patients developed high-grade glial tumor (n: 7) and medulloblastoma (n: 2). The affected genes in the three families were MSH6 [c.478C > T (p.Gln160Ter)], MSH6 [c.2871dupC (p.Phe958LeufsTer5)] and MLH1 [c.236G > A(p.Arg79Lys)], respectively. Seven patients had multiple developmental venous anomalies; six patients had leptomeningeal enhancement; and five patients had cavernomas. None of these findings were present in the group without CMMRD. Conclusions. Constitutional mismatch repair deficiency should be considered when multiple developmental venous anomalies, cavernomas, and leptomeningeal enhancement are detected, especially in patients with café au lait spots.
Keywords: cavernomas; central nervous system tumor; constitutional mismatch repair deficiency; developmental venous anomalies; leptomeningeal enhancement